2011
DOI: 10.1007/978-3-642-21444-8_20
|View full text |Cite
|
Sign up to set email alerts
|

OLSRp: Predicting Control Information to Achieve Scalability in OLSR Ad Hoc Networks

Abstract: Abstract. Scalability is a key design challenge that routing protocols for ad hoc networks must properly address to maintain the network performance when the number of nodes increases. We focus on this issue by reducing the amount of control information messages that a link state proactive routing algorithm introduces to the network. Our proposal is based on the observation that a high percentage of those messages is always the same. Therefore, we introduce a new mechanism that can predict the control messages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Medina et al [12] showed that Topology Control (TC) messages, which are used to distribute information about the local neighborhood in the network, tend to be similar over longer periods. This indicates that the neighborhood has not changed and thus also similar HELLOs were exchanged.…”
Section: B Refresh Methodsmentioning
confidence: 99%
“…Medina et al [12] showed that Topology Control (TC) messages, which are used to distribute information about the local neighborhood in the network, tend to be similar over longer periods. This indicates that the neighborhood has not changed and thus also similar HELLOs were exchanged.…”
Section: B Refresh Methodsmentioning
confidence: 99%
“…These communication limitations have frequently been addressed using mobile ad hoc or opportunistic networks, as well as routing protocols on these networks [4][5][6]. These networks have low bandwidth and their topology is highly dynamic, and as such, they require the exchange of an goals, e.g., to support message delivery in mobile ad hoc networks (MANETs) [25][26][27][28], reduce the traffic [29][30][31] and keep the energy consumption in these infrastructures under control [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the prediction of topology propagation (TP) messages based on historical information, in previous works, the authors have shown that the traffic generated by a link-state routing protocol, like OLSR [35], grows almost exponentially with the number of nodes when different node densities are considered in the analysis [29,30]. Therefore, a network with a large number of nodes requires the exchange of a huge amount of TP messages to inform the nodes about the topology changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a proposal was based on Optimized Link State Routing with prediction (OLSRp) [8] and it included adaptations to be used on a HWSN. The evaluation of such a topology prediction strategy showed promising results in terms of energy savings; however it considered only a particular work scenario.…”
Section: Introductionmentioning
confidence: 99%